Palm Stearin as Alternative Binder for MIM: A Review - Arifin, Amir; Sulong, Abu Bakar; Mohruni, Amrifan Saladin; Yani, Irsyadi; Gunawan, Gunawan (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2014)
Palm stearin is one of the fractionation process results from palm oil that is the largest commodities in the world. It has potentially as an alternative of binder in metal injection molding based on researches that conducted in Malaysia. Palm stearin can be combined with other binder to be a binder system with the function as lubricant and surfactant in a binder system. Based on experiments showed Palm stearin has fulfilled requirement as binder in MIM such as pseudoplastic behavior from rheological test and homogeneity of the feedstock. Palm stearin can replace conventional binders that commonly used in industry.